Funkcional'nye i strukturnye svojstva myscc niznych konecnostej u sportsmenov s razlicnoj napravlennost'ju trenirovocnogo processa - Scurov, V. A.; Elizarova, S. N.; Grebenok, L. A. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The purpose of the research was to find-out the features of frame of muscles of an anticnemion in the athletes training quality of endurance, and athlete with the power orientation of training process, and also interrelation of frame and contractile abilities of muscles. The higher contractile ability of muscles, depth of muscles and an angle of an inclination of muscle bundles have been revealed in the athletes. These parameters are closely interconnected among themselves. The feature of the structural state of muscles in athletes is their best vascularization and rather smaller sizes of an accretion of an angle of an inclination of muscle bundles at contractility. Linear rate of a blood-groove on arteries of an extremity at the moment of the terminal of the functional trial enlarged not less than by 20 % and most quickly comes back to the reference values in athletes.